Respuesta :
Let h be the height of the triangle. With this the base may be represented as 7h - 2. The area of the triangle is half the product of its base and height. Therefore,
A = (1/2)bh = (1/2)(7h - 2)h
Substitute to the equation the value of h,
A = (1/2)((7)(14 cm) - 2)(14 cm)
A = 672 cm²
A = (1/2)bh = (1/2)(7h - 2)h
Substitute to the equation the value of h,
A = (1/2)((7)(14 cm) - 2)(14 cm)
A = 672 cm²
Answer:
[tex]A(h)=\frac{7}{2}h^{2}-h(cm)[/tex]
The area of the triangle is [tex]672cm^{2}[/tex] when the height is 14 cm.
Step-by-step explanation:
We start by finding the function rule for the area A.
We know reading the exercise that ''The base b is 2 cm less than seven times the height h''
Let's turn this into an equation :
[tex]b=7h-2cm[/tex] (I)
The area of a triangle is [tex]\frac{b.h}{2}[/tex] (II)
Given that ''b'' is the base and ''h'' is the height.
Now we replace (I) in (II).
[tex]A=\frac{b.h}{2}=\frac{(7h-2cm).h}{2}=\frac{7h^{2}-2h(cm)}{2}=\frac{7}{2}h^{2}-h(cm)[/tex]
The area A is a function of the variable ''h''
[tex]A(h)=\frac{7}{2}h^{2}-h(cm)[/tex]
That is the function rule for the area A.
To find the area when the height is 14 cm we replace in the function rule h by 14 cm ⇒
[tex]A(14cm)=\frac{7}{2}(14cm)^{2}-14cm(cm)=686cm^{2}-14cm^{2}=672cm^{2}[/tex]
The area of the triangle is [tex]672cm^{2}[/tex] when the height is 14 cm.